Scientific Temperament of Farmers and Their Correlates (Indian Journal of Extension Education, 2014)
This investigation attempted to identify the factors which determine the scientific temperament of farmers. An exhaustive survey was conducted in 5 Blocks of Saran district of Bihar. It was found that education, social participation, farm size, farm power, farm Implements and irrigation potentiality were positively and significantly related to communication behaviour and scientific temperament of farmers at 5 per cent level of significance. Age and credit behaviour were not significantly related to scientific temperament.